An integrated behavior change model for physical activity - Hagger, Martin; Chatzisarantis, N. (Lippincott Williams and Wilkins, 2014)
We present the Integrated Behavior Change Model, a comprehensive multi-theory model outlining the psychological factors and processes that impact physical activity behavior. The model integrates hypotheses from social-cognitive, motivational, dual-phase, and dual-systems theories. We provide the theoretical basis for the model and demonstrate its utility in driving future research and developing effective interventions to promote physical activity.